3d-electrons contribution to cohesive energy of 3d-metals - Didukh, L. (Condensed Matter Physics, 2018)
In this paper a model for 3d-subsystem of transition 3d-metals has been proposed and used for calculation of the cohesive energy dependent on 3d-band filling of particular metal, its bandwidth and effective intra-atomic interaction value. It has been shown that the model enables one to explain the observed peculiarities of cohesive energy effect on the atomic number. The nature of two parabolic dependencies of cohesive energy on 3d-band filling has been clarified. The calculated values of cohesive energy are close to those experimentally obtained for Sc-Ti-V-Cr-Mn-Fe series. В роботi запропоновано модель пiдсистеми 3d-електронiв перехiдних металiв та застосовано її для розрахунку енергiї зв’язку, залежної вiд заповнення 3d-зони конкретного металу, ширини цiєї зони та величини ефективної внутрiшньоатомної взаємодiї. Показано, що модель дозволяє пояснити спостережуванi особливостi залежностi енергiї зв’язку вiд атомного номера. Пояснено природу двох параболiчних залежностей енергiї зв’язку вiд заповнення 3d-зони. Обчисленi значення енергiї зв’язку є близькими до отриманих експериментально для ряду Sc-Ti-V-Cr-Mn-Fe.